2021
DOI: 10.13189/cea.2021.090313
|View full text |Cite
|
Sign up to set email alerts
|

Review of Aerodynamic Design Configurations for Wind Mitigation in High-Rise Buildings: Two Cases from Amman

Abstract: This study is concerned with reviewing and analyzing methods used in early design stages to mitigate wind effects on high-rise buildings. In order to mitigate wind effects on structures and specifically high-rise buildings, early stage aerodynamic design decisions are made. Architects try to mitigate the wind effects on buildings by choosing the right form configuration like tapering or setbacks, etc., or by making vital decisions in the early design stage. However, structural engineers utilize the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…It was observed that small corner modification ratios reduced wind forces more effectively than their larger counterparts (Tse et al , 2021). Najjar and Azhari (2021) investigated wind effects on different aerodynamic design configurations in high-rise buildings. They analyzed the problem in both architecture and civil engineering perspective (Najjar and Azhari, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that small corner modification ratios reduced wind forces more effectively than their larger counterparts (Tse et al , 2021). Najjar and Azhari (2021) investigated wind effects on different aerodynamic design configurations in high-rise buildings. They analyzed the problem in both architecture and civil engineering perspective (Najjar and Azhari, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Najjar and Azhari (2021) investigated wind effects on different aerodynamic design configurations in high-rise buildings. They analyzed the problem in both architecture and civil engineering perspective (Najjar and Azhari, 2021). Jendzelovsky and Antal (2021) studied wind pressure distribution on the high-rise building in the shape of an equilateral acute triangle.…”
Section: Introductionmentioning
confidence: 99%